I would be better off dead: investigating suicidal ideation in people with epilepsy - Gloria Maria de Almeida Souza Tedrus; Daniela de Carvalho Mendonça de Souza (Arquivos de Neuro-Psiquiatria)
Background It is known that the risk of suicidal behavior in adult people with epilepsy (PWEs) is high. However, the associated clinical and psychosocial factors are still being discussed. Objective To assess the risk of suicide in PWEs and relate it to resilience and quality of life (QoL) as well as with clinical variables. Methods The item “I'd be better off dead” of the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E) was related to the resilience scale, clinical aspects, the presence of depression, and the Quality of Life in Epilepsy Inventory (QOLIE-31) scores of PWEs, with a p < 0.05. Results A total of 271 PWEs were assessed, 50.6% were female, with a mean age of 46.6 (± 15.8) years, and a mean age at 1st seizure of 24.1 (± 18.5) years. Risk for suicide occurred in 50 (19.3%) cases. In multiple logistic regression, the factors that explain the risk of suicide were female sex, depression, and lower scores on the QOLIE-31 and on the resilience scale. In the classification and regression trees, the order of importance of the variables was depression > resilience > age > QoL > age at 1st seizure. Conclusion The risk of suicide was high, and it was associated with demographic aspects, clinical variables, QoL, and resilience. A higher risk of suicide was associated with lower resilience regardless of the presence or absence of depression. In the presence of depression, a higher risk of suicide was associated with the early onset of epilepsy. In the absence of depression, the risk of suicide was associated with low QoL in young adults.